Quantitative Trait Loci Mapping of Mineral Element Contents in Brown Rice Using Backcross Inbred Lines Derived From Oryza longistaminata - Liu, Xingdan; Fan, Fengfeng; Liu, Manman; Long, Weixiong; Yu, Yajie; Yuan, Huanran; Pan, Guojing; Li, Nengwu; Li, Shaoqing; Liu, Jianfeng (Frontiers in Plant Science, 2020)
Mineral elements play an extremely important role in human health, and are worthy of study in rice grain. Wild rice, as an important gene pool for rice improvement in grain yield, disease and pest resistance as well as mineral elements. In this study, we identified 28 novel quantitative trait loci (QTL) for content of six mineral elements in wild rice Oryza longistaminata. Interestingly, these QTL exhibited significant co-location, including qSe1/qCd1 on chromosome 1, qCd4.2/qHg4 on chromosome 4, qFe5.2/qZn5.2 on chromosome 5, qFe9.2/qZn9.3/qAs9 on chromosome 9 and qCd10/qHg10/qAs10 on chromosome 10. Among them, qSe1/qCd1, one of the co-localizing sites that can significantly improve the Se content while reducing the Cd content, was delimited to an interval about 53.8 Kb on chromosome 1. qFe5.2/qZn5.2, another co-localizing sites which can significantly improve the Fe and Zn content, was located in a region about 26.2 Kb on chromosome 5. These QTL derived from wild rice Oryza longistaminata will provide new insights into the genetic mechanism of mineral element accumulation, and establish the basis for subsequent gene cloning and mineral element composition improvement in rice grains.